TECHNOLOGY AND ON SERVICE QUALITY IN THE CLEANING INDUSTRY: A CASE STUDY - Talib, Ameen; Mustakin, Abdul Fareed (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
This study focuses on the commercial cleaning industry. This study explores and cross-examines two commercial cleaning companies, one of which is tech-enabled in its service processes and performance while the other, operates traditionally without the use of any service control strategies. This study adopted a two-pronged approach in examining the implications of technology on service quality in the cleaning industry. A case study methodology was firstly used to explore, discover and cross-examine qualitative insights in the service design of both Company A and Company B. Subsequently, the servqual methodology was applied to provide empirical support on whether the use of technology has a positive effect on service quality. The results from the servqual method contradicts with the finding of the case study, The servqual method suggests that there may not be a difference in the service quality of a tech-enabled service company and a traditional service company. On the contrary, the case studies revealed implicit variabilities that exist between the service delivery of the two companies.